PERAN GURU DALAM PENCEGAHAN PERILAKU KEKERASAN DI SMA NEGERI 2 SEUNAGAN NAGAN RAYA - Ricky Dear Fitria (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2020)
The role of the teacher relates to how a teacher is able to understand and determine the limits that must be done in organizing material, interacting and doing the learning process. Violent behavior is the use of force or force with the aim of hurting a weaker person or group, so that the victim feels depressed or traumatized and helpless. This study aims to determine the role of teachers in preventing violent behavior in Sma Negeri 2 Seunagan Nagan Raya. This research is descriptive with cross sectional study approach through total sampling technique. Research data collection was carried out on 11 to 8 December 2019 in SMA 2 Seunagan Nagan with a total of 28 respondents, data collection tools used in the form of a questionnaire scale consisting of 20 question items. Data analysis is presented in the form of a frequency distribution table. The results showed that 64.3% had a teacher's role as a corrector for the prevention of violent behavior in schools, 60.7% had a teacher's role as an informer for the prevention of violent behavior in schools, 78.6% had a teacher's role as a class manager for preventing violent behavior in schools . Based on these data, there is a teacher's role in preventing violent behavior in schools, so the researchers suggest maintaining a good role in providing guidance to students at school. Keywords: Teacher Role, Prevention, Violent Behavior (Bullying)